Pengembangan buletin digital berbasis flipbook untuk meningkatkan keterampilan berpikir kritis pada mata pelajaran IPAS siswa sekolah dasar - Anita Anita; Encep Andriana; Laksmi Evasufi Widi Fajari (Trihayu: Jurnal Pendidikan Ke-SD-an, 2026)
Twenty-first-century education emphasizes the integration of knowledge and technology in the learning process to prepare students to live, adapt, and contribute effectively amid rapid technological development, globalization, and increasing social complexity. This study aims to describe the development process of a flipbook-based digital bulletin, assess the feasibility of the developed media, and determine the improvement in students’ critical thinking skills after using the media. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The results showed that: (1) the flipbook-based digital bulletin on fauna in Ujung Kulon National Park was successfully developed through the stages of the ADDIE model; (2) the use of the flipbook-based digital bulletin improved students’ critical thinking skills in Natural and Social Sciences (IPAS) learning, particularly on the topic of fauna in Ujung Kulon National Park; and (3) the developed digital bulletin was categorized as highly feasible for use in the learning process to support the development of students’ critical thinking skills. Therefore, the flipbook-based digital bulletin can serve as an alternative instructional medium for Natural and Social Sciences learning that supports the development of students’ critical thinking skills.